Evolving Dynamics of Moderate Islamic Discourse on Indonesian Social Media - Ghufron Hamzah; Ahmad Muttaqin; Muhammad Irsad; Fouad Larhzizer (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Social media not only creates a new public sphere for the expression of religious activities but also serves as a contested arena for religious discourse. In Indonesia, one of the key discourses under contention is moderate Islamic discourse. This article addresses two primary questions: First, what forms does contested moderate Islamic discourse take on social media, and what strategies are employed in these contests?.  Second, what factors contribute to the emergence of these contestations surrounding moderate Islamic discourse on social media?. Using Fairclough’s critical discourse analysis as a theoretical framework, this research explores qualitative data gathered through the observation of YouTube videos. The findings indicate that the contestation of moderate Islamic discourse on YouTube occurs not only between traditional and new religious authorities, as is often assumed, but also among traditional religious authorities themselves. These groups compete to articulate the true and ideal meaning of moderate Islam. The contestation is driven by a combination of ideological, economic, political, and socio-cultural factors that influence the digital sphere in Indonesia.